Early-Stage Repetitive Transcranial Magnetic Stimulation Altered Posterior–Anterior Cerebrum Effective Connectivity in Methylazoxymethanol Acetate Rats - Guo, Huiling; Xiao, Yao; Sun, Dandan; Yang, Jingyu; Wang, Jie; Wang, Huaning; Pan, Chunyu; Li, Chao; Zhao, Pengfei; Zhang, Yanbo; Wu, Jinfeng; Zhang, Xizhe; et al. (Frontiers in Neuroscience, 2021)
The aim of current resting-state functional magnetic resonance imaging (fMRI) study was to investigate the potential mechanism of schizophrenia through the posterior-anterior cerebrum imbalance in methylazoxymethanol acetate (MAM) rats and to evaluate the effectiveness of repetitive transcranial magnetic stimulation (rTMS) as an early-stage intervention. The rats were divided into four groups, MAM-sham group, vehicle-sham group, MAM-rTMS group and vehicle-rTMS group. The rTMS treatment was targeted in the visual cortex in adolescent rats. Granger Causality Analysis (GCA) was used to evaluate the effective connectivity between regions of interest. Results demonstrated a critical right visual cortex (VC) -nucleus accumbens (Acb) -orbitofrontal cortex (OFC) pathway in MAM rats; significant differences of effective connectivity (EC) were found between MAM-sham & vehicle-sham groups (from Acb shell to OFC: t=-2.553, p=0.021), MAM-rTMS & MAM-sham groups (from VC to Acb core: t=-2.206, p=0.043; from Acb core to OFC: t=4.861, p<0.001; from Acb shell to OFC: t=4.025, p=0.001) and MAM-rTMS & vehicle-rTMS groups (from VC to Acb core: t=-2.482, p=0.025; from VC to Acb shell: t=-2.872, p=0.012; from Acb core to OFC: t=4.066, p=0.001; from Acb shell to OFC: t=3.458, p=0.004) in right hemisphere. Results of the early stage rTMS intervention revealed that right nucleus accumbens played the role as a central hub, and visual cortex was a potentially novel rTMS target region during adolescent schizophrenia. Moreover, the EC of right nucleus accumbens shell and orbitofrontal cortex was demonstrated to be a potential biomarker. To our knowledge, this was the first resting-state fMRI study using GCA to assess the deficits of a visual-reward neural pathway and the effectiveness of rTMS treatment in MAM rats. More randomized controlled trials in both animal models and schizophrenia patients are needed to further elucidate the disease characteristics.